Syriac Spells for a Mill and Their Historical Context - Cherkashina, Anna; Cherkashin, Dmitry; Saʿar, Orṭal-Paz 1975- (2022)
This article considers a text-unit known in five Syriac codices and consisting of up to three magical recipes. The target of all these recipes is a mill: two of them are curses (ˀassārā ‘binding spell’) and intend to stop the mill, while the third one is a counter-spell (šeryānā ‘loosening spell’), which aims to annul the curse. One of the two binding spells includes a rare example of an Arabic incantation written in Garshuni. The main purpose of this article is to make these texts available via critical editions. In addition, light is shed on the broader context of magical practices, by drawing attention to Syriac recipes for an oven and their Jewish parallels, and by presenting two Jewish parallels of spells related to a mill: a Judaeo-Arabic text from the Cairo Genizah and a spell from a Byzantine manuscript. We offer a reconsideration of the interpretation of the Judaeo-Arabic text, as our reading differs from that of the Editio Priceps.
Keywords: Aramaic; Judaeo-Arabic; Cairo Geniza; Garshuni; Syriac-Arabic; Magic; binding spell; Book of Protection; Syriac charms